Contribution of plasma AT III levels to the diagnosis and prognostic evaluation of liver cirrhosis - Mehmet İŞLER and Nadir YÖNETÇİ and Abdi SAĞCAN and Hakan YÜCEYAR and Yücel BATUR (Turkish Journal of Gastroenterology, 2020)
-